Program evaluation of southeast sulawesi student sports center for development and training - isa, la ode; Lubis, Johansyah; Sujiono, Bambang (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this study was to determine the results of the evaluation of the Southeast Sulawesi Student Sports Training and Development Center which included the components of context, input, process and product. This research is a type of evaluation research through a quantitative and qualitative approach. Program evaluation is carried out to determine the achievement of the targets that have been set. Then make a decision on the program. In the program evaluation research using the CIPP evaluation model, namely context, input, process, product. The four evaluation aspects are used to determine the implementation of the Southeast Sulawesi Student Sports Training and Development Center Program. The research subjects selected were stakeholders as many as 30 respondents, namely athletes, coaches, and the Head of the Southeast Sulawesi Youth and Sports Office. Apart from informants from the stakeholders, the subjects of this research are documents related to the Southeast Sulawesi Student Sports Training and Development Center Program.